Epigenetic modifications in chronic rhinosinusitis with and without nasal polyps - Li, Jing; Qiu, Chang-Yu; Tao, Yue-Jin; Cheng, Lei (Frontiers in Genetics, 2023)
Chronic rhinosinusitis (CRS) has brought a huge socioeconomic burden. However, its mechanism is still elusive, which may involve genetic, environmental and some other factors. Epigenetic analyses have been conducted to explore the mechanisms underlying CRS. Here, we reviewed the fruits in the epigenetic studies on DNA methylation, histone modification, and noncoding RNA regulation. We concluded that the epigenetic research on CRS has made great breakthroughs, especially in the past five years and the field of microRNAs. “Epigenetic therapies” are expected to be designed to treat CRS in the future.